2010
DOI: 10.5005/jp-journals-10018-1194
|View full text |Cite
|
Sign up to set email alerts
|

Complete Eradication of Bleeding Duodenal Varices with Endoscopic Polydocanol Sclerotherapy

Abstract: Bleeding from duodenal varices is a rare complication of portal hypertension, occurring in only 0.4% of these patients and is often life-threatening because of the difficulty in diagnosis and treatment. Treatment options include surgical procedures and endoscopic and endovascular treatments. A 48-year-old female cirrhotic patient was admitted to our clinic with upper gastrointestinal (GI) tract bleeding. Endoscopic examination revealed nonbleeding Lm, Cb, RC (+), F3-F3-F2 esophageal and nodular-bleeding-oozing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Our initial search yielded 395 case reports of SIV in patients with cirrhosis, of which 76 (19.2%) reported SIV bleeding and were included for collation and analysis (9–20,21–30,31–40,41–50,51–60,61–78). Mean age was 52.4 years (range 40–68), 32 were women, and 44 were men.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial search yielded 395 case reports of SIV in patients with cirrhosis, of which 76 (19.2%) reported SIV bleeding and were included for collation and analysis (9–20,21–30,31–40,41–50,51–60,61–78). Mean age was 52.4 years (range 40–68), 32 were women, and 44 were men.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of DV is aimed at occlusion of the portal venous perforators as opposed to arterial embolization used in non-variceal, peptic ulcer bleeding. The current therapeutic options include endoscopic varix band ligation (EVL), TIPS, percutaneous transhepatic obliteration, balloon-occluded retrograde transvenous obliteration, and surgery [ 5 , 6 ]. However, given the scarcity of literature, there is a lack of consensus regarding a standard treatment approach for DV.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the scarcity of literature, there is a lack of consensus regarding a standard treatment approach for DV. The most common therapeutic intervention is EVL, although the rebleeding risk remains high due to the minimal thickness of the duodenal wall [ 6 ]. One study evaluating the effectiveness of EVL for the treatment of DV found the overall success rate to be low at approximately 16% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some cases may be refractory to the band given the anatomy of the duodenal varices [ 46 ]. Sclerosants and tissue adhesives were injected into target intravarices or feeding collateral vessels to obtain the eradication of varices [ 57 – 59 ]. Third, in published studies, sclerosants and tissue adhesives included ethanolamine oleate, sodium morrhuate, absolute alcohol, polidocanol, thrombin, cyanoacrylate, and sodium tetradecyl sulfate; in addition, cyanoacrylate and ethanolamine oleate are frequently used.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic treatment techniques theoretically increase the risk of mucosal ulcers, perforations, or other complications given the relative thinness of the duodenal wall compared to the other parts of the upper gastrointestinal tract [ 46 , 57 , 61 ]. In this systematic review, the overall rate of adverse events was 27.7%, which was comparable with 19–38% previously reported for endoscopic treatments for gastric varices [ 62 64 ].…”
Section: Discussionmentioning
confidence: 99%